1999
DOI: 10.1007/bf02784423
|View full text |Cite
|
Sign up to set email alerts
|

Elemental composition of human milk from mothers of premature and full-term infants during the first 3 months of lactation

Abstract: To examine longitudinal and gestational effects of mineral content in human milk, we analyzed human milk from lactating mothers of premature (PRT, n = 24, < 2000 g birth weight, < 37 wk gestation) and full-term (FT, n = 19, > 2500 g, 39-41 wk gestation), living in Newfoundland, Canada. Samples were collected once a week for 8 wk with one final sample collected at 3 mo. Milk samples collected in acid-washed containers were wet ashed with concentrated HNO3, and barium, cadmium, calcium, cesium, cobalt, copper, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
39
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 24 publications
8
39
2
Order By: Relevance
“…A study by Friel et al 1999 reported La content at around 5 μg L −1 which is consistent with our findings. Similar values were reported for Ce (Friel et al 1999), an element found below detection in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A study by Friel et al 1999 reported La content at around 5 μg L −1 which is consistent with our findings. Similar values were reported for Ce (Friel et al 1999), an element found below detection in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…A study by Friel et al 1999 reported La content at around 5 μg L −1 which is consistent with our findings. Similar values were reported for Ce (Friel et al 1999), an element found below detection in the present study. Colostrum milk has been previously shown to contain significantly higher concentrations of various trace elements, including essential and toxic ones, than transitional or mature breast milk (Akanle et al 2001;Chao et al 2014).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Molybdenum concentrations of human milk appear to be highest during the first few days of breastfeeding, and decrease during the course of lactation (Dang et al, 1984;Casey and Neville, 1987;Bouglé et al, 1988;Aquilio et al, 1996;Krachler et al, 1998;Friel et al, 1999) (Appendix A). In mature human milk 6 from women in Europe, mean molybdenum concentrations were reported to range from 0.72 to 4 µg/L.…”
Section: Breast Milkmentioning
confidence: 99%
“…During lactation in rats, there is a 20-fold increase in transport of plasma copper to the mammary gland (Donley et al 2002). Copper concentrations in milk are high after birth (0.4-0.6 mg/liter in humans) but decrease during late lactation both in humans (0.2-0.3 mg/liter) (Perrone et al 1993;Lö nnerdal 1996;Wooten et al 1996;Friel et al 1999) and rodents (Linder et al 1998). The supply of copper to milk may be regulated by hormonal control of copper fluxes into and out of the mammary gland during lactation.…”
mentioning
confidence: 99%